Quranic literary study: Sayyid qutb’s thought and orientation - Daud, Ismail; Nooraihan, Ali; Asyraf, Hj Ab Rahman (Canadian Center of Science and Education, 2015)
This paper looks into Sayyid Qutb’s thought and his personal experiences in regards to the study of the Quran including its content and literary aspects during the years 1940 to 1945 and how this new orientation have had a great impact on Qutb’s later writings. Data for the study is based on Qutb’s works such as al Taswir al Fanni fil Quran, al Adalah al Ijtimaiyyah fil-Islam and Fi Zilal al Quran. These works considered fundamental and paramount in analysing Qutb’s thought throughout those years as the Quran gradually motivated Qutb and his later views in regards to Islam and society as a whole. A descriptive analysis is employed by examining his works which manifest Qutb’s thought besides identifying some major themes relevant to the study objectives.